Effects of SiC amount and morphology on the properties of TiB2-based composites sintered by hot-pressing. Issue 11 (1st August 2020) - Yan, Shu-Rong; Lyu, Zongjie; Foong, Loke Kok
Abstract: This investigation intended to assess the influence of SiC morphology on the sinterability and physical-mechanical features of TiB2 -SiC composites. For this aim, different volume percentages of SiC particles and SiC whiskers were introduced to TiB2 samples hot-pressed at 1950 °C for 2 h under an external pressure of 25 MPa. The characterization of as-sintered specimens was carried out using X-ray diffraction, optical microscopy, and scanning electron microscopy. The relative density studies revealed that SiCw had a more significant impact on the sinterability of TiB2 -based composites. The XRD investigation confirmed the production of an in-situ TiC phase during the hot-pressing; however, some peaks related to the graphitized carbon also appeared in the patterns of SiCw -doped ceramics. The addition of 25 vol% SiCp halved the average grain size of TiB2 while introducing the same content of SiCw decreased this value by just around 20%. Finally, the highest Vickers hardness and fracture toughness were obtained for the sample reinforced with 25 vol% SiCw, standing at 29.3 GPa and 6.1 MPa m 1/2, respectively.